Heroin initiation and risk : an ethno-epidemiological approach - Cronly, Jennifer (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2011)
This thesis provides an in-depth exploration into the process of heroin and injecting initiation among young people in Ireland. It also presents a detailed investigation of risk perception and behaviour during the early heroin and injecting career. Rather than providing an individualistic account that primarily identifies and locates the causes of behaviour within the individual, this study adopts a 'risk environment' framework (Rhodes 2002. 2009). It seeks therefore, to explore the environmental forces and social processes that both contextualise and shape young people's risk behaviour and their pathways to heroin and injecting drug use. The principle aim is to present the views and subjective experiences of young recent heroin or injecting initiates in order to capture the social organisation and construction of risk.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin